Desiccation Tolerance in Chlorophyllous Fern Spores: Are Ecophysiological Features Related to Environmental Conditions? - López-Pozo, Marina; Ballesteros, Daniel; Laza, José Manuel; García-Plazaola, José Ignacio; Fernández-Marín, Beatriz (Frontiers in Plant Science, 2019)
Fern spores of most species are desiccation tolerant (DT) and, in some cases, are photosynthetic at maturation, the so-called chlorophyllous spores (CS). The lifespan of CS in the dry state is very variable among species. The physiological, biochemical, and biophysical mechanisms underpinning this variability remain understudied and their interpretation from an ecophysiological approach virtually unexplored. In this study, we aimed at fulfilling this gap by assessing photochemical, hydric, and biophysical properties of CS from three temperate species with contrasting biological strategies and longevity in the dry state: Equisetum telmateia (spore maturation and release in spring, ultrashort lifespan), Osmunda regalis (spore maturation and release in summer, medium lifespan), Matteuccia struthiopteris (spore maturation and release in winter, medium-long lifespan). After subjection of CS to controlled drying treatments, results showed that the three species displayed different extents of DT. CS of E. telmateia rapidly lost viability after desiccation, while the other two withstood several dehydration–rehydration cycles without compromising viability. The extent of DT was in concordance with water availability in the sporulation season of each species. CS of O. regalis and M. struthiopteris carried out the characteristic quenching of chlorophyll fluorescence, widely displayed by other DT cryptogams during drying, and had higher tocopherol and proline contents. The turgor loss point of CS is also related to the extent of DT and to the sporulation season: lowest values were found in CS of M. struthiopteris and O. regalis. The hydrophobicity of spores in these two species was higher and probably related to the prevention of water absorption under unfavorable conditions. Molecular mobility, estimated by dynamic mechanical thermal analysis, confirmed an unstable glassy state in the spores of E. telmateia, directly related to the low DT, while the DT species entered in a stable glassy state when dried. Overall, our data revealed a DT syndrome related to the season of sporulation that was characterized by higher photoprotective potential, specific hydric properties, and lower molecular mobility in the dry state. Being unicellular haploid structures, CS represent not only a challenge for germplasm preservation (e.g., as these spores are prone to photooxidation) but also an excellent opportunity for studying mechanisms of DT in photosynthetic cells.